An intervention for improving the lifestyle habits of kindergarten children in Israel: a cluster-randomised controlled trial investigation. Issue 9 (12th March 2014) - Lerner-Geva, Liat; Bar-Zvi, Elinor; Levitan, Gila; Boyko, Valentina; Reichman, Brian; Pinhas-Hamiel, Orit
Abstract: Objective: To assess the effectiveness of an intervention programme to improve kindergarten children's eating and leisure habits in Israel. Design: A cluster-randomised controlled trial. Setting: Six full-day kindergartens in Israel were randomly divided into three groups. Group A received the full intervention programme, which included lessons on good eating habits and daily physical exercise. Group B received a partial intervention of lessons only. Group C, the reference group, did not receive any intervention. Subjects: Children aged 4–6 years ( n 204) were recruited for the study. Methods: Objective data for weight and height were collected to calculate BMI Z -scores. Activity, sedentary time, sleeping hours and daily energy intake were assessed via a parental questionnaire. Nutritional knowledge was assessed by a single dietitian using a questionnaire addressed to the children. Assessments were done at baseline and at the end of the intervention. Results: After adjustment for baseline levels we observed a significant reduction in daily energy intake for the full intervention group A ( P = 0·03). A positive intervention effect was demonstrated on nutritional knowledge in the partial intervention group B ( P = 0·03), although no significant change was demonstrated for BMI Z -score. Conclusions: The study supports the incorporation of education on healthy lifestyle habits and physical activity into the curricula of kindergartens.